Avoiding a looming crisis: novice leader preparation and retention - Seegmiller, Daniel P., author; Cooner, Donna, advisor; Fothergill, Wendy, committee member; Frederiksen, Heidi, committee member; O'Donnell-Allen, Cindy, committee member (Colorado State University. Libraries, 2021)
The purpose of this case study was to identify key components, along a continuum of preparation, that school districts and university partners could provide to enhance the support and retention of novice educational leaders in the first three years in their roles. Additionally, the case study identified components missing from an educational administrator licensure program that could be included or addressed to provide a more comprehensive preparation. The research was set within a constructivist, and specifically phenomenological, paradigm. This paradigm provided the understanding that each participant in the study has a different experience and view of the preparation they received through their principal licensure program and how that preparation did, or did not, prepare them for the realities of their first three years in their roles as educational leaders. This case study was explored through focus groups that allowed both the participants and the facilitator to better understand the experiences of each individual involved and co-create an understanding of how future educational leaders can be better prepared and supported as new leaders. Novice leader preparation and retention is an issue requiring a greater level of awareness so that action may be taken to mitigate its unfortunate effects on student outcomes and achievement, staff stability and effectiveness, equity and inclusion, increasingly limited candidate pool, and the career longevity of those seeking to lead our schools in a time of intensifying pressure and complexity.
Keywords: leadership; principal; support; preparation; education; retention; school principals; burnout; school leadership; stress; self-efficacy; principal retention; principal selection; equity leadership; principal shortage